Serum interleukin-38 levels correlated with insulin resistance, liver injury and lipids in non-alcoholic fatty liver disease - Jun Cao; Lin Hua; Shipei Zhang; Jinping Tang; Fan Ke; Zhouhuan Wu; Guohui Xue (Lipids in Health and Disease, 2022)
Abstract Background Insulin resistance, liver injury and dyslipidemia are reported in non-alcoholic fat liver disease (NAFLD) patients. Interleukin (IL)-38 may take part in the pathophysiology of insulin resistance. Nevertheless, the function of IL-38 in NAFLD is unknown. Herein, we determined whether serum IL-38 level might be utilised as a biochemical marker for diagnosing NAFLD. Methods NAFLD patients and healthy participants (n = 91 each) were enrolled. Circulating serum IL-38 levels were detected using enzyme-linked immunosorbent assay. Other metabolic and inflammatory indices related to NAFLD were also assessed. Results Patients with NAFLD had higher serum IL-38 levels than healthy individuals. Significantly higher serum IL-38 levels were found in patients with severe and moderate NAFLD than in patients with mild NAFLD. IL-38 showed a significant correlation with parameters of insulin resistance, inflammation, and liver enzyme in NAFLD cases. Anthropometric, insulin resistance, inflammatory parameters, lipids and frequency of NAFLD showed significant differences among the serum IL-38 level tertiles. Participants in the 2nd and 3rd tertiles of serum IL-38 levels had a greater risk of NAFLD than those in the 1st tertile. Furthermore, IL-38 ROC curve showed a high area under ROC with 0.861. Conclusions It is possible for serum IL-38 to be a biomarker for NAFLD.